Clinical and Onychoscopy Patterns in Fingernail Onychomycosis—A Study by the International Dermoscopy Society Trichoscopy And Onychoscopy Task Force - Matilde Iorizzo; Bianca Maria Piraccini; Aurora Alessandrini; Francesca Bruni; Laura Vollono; Francesca Pampaloni; Nilton Gioia Di Chiacchio; Nilton Di Chiacchio; Juan Jimenez-Cahue; Chander Grover; Zoe Apalla; Asmahne Souissi; et al. (Dermatology Practical & Conceptual)
Introduction: Onychomycosis is one of the most common nail diseases. Fingernail onychomycosis is significantly less frequent than toenail onychomycosis and it is often misdiagnosed due to its subtle clinical presentations.